2015
DOI: 10.18632/oncotarget.4361
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA UCA1 induces non-T790M acquired resistance to EGFR-TKIs by activating the AKT/mTOR pathway in EGFR-mutant non-small cell lung cancer

Abstract: The aim of this study was to explore the role of long non-coding RNA UCA1 (urothelial cancer-associated 1) in acquired resistance to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) in EGFR-mutant non-small cell lung cancer (NSCLC). In our study, UCA1 expression was significantly increased in lung cancer cells and patients with acquired resistance to EGFR-TKIs. Over-expression of UCA1 was significantly associated with a shorter progression-free survival (PFS) [13.0 vs. 8.5 months, P < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
126
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 45 publications
2
126
0
Order By: Relevance
“…We have identified some lncRNAs including lncRNA UCA1, H19, BC200 and BC087858 were up-regulated in gefitinib-resistant human lung cancer cells by lncRNA microarray analysis [18]. Also we have demonstrated that lncRNA UCA1 may induce non-T790M acquired resistance to EGFR-TKIs by activating the AKT/mTOR pathway and EMT [24]. However, the role and mechanisms of lncRNA BC087858 in EGFR-TKIs acquired resistance remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified some lncRNAs including lncRNA UCA1, H19, BC200 and BC087858 were up-regulated in gefitinib-resistant human lung cancer cells by lncRNA microarray analysis [18]. Also we have demonstrated that lncRNA UCA1 may induce non-T790M acquired resistance to EGFR-TKIs by activating the AKT/mTOR pathway and EMT [24]. However, the role and mechanisms of lncRNA BC087858 in EGFR-TKIs acquired resistance remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should focus on the clinical utility of UCA1 -based cancer diagnosis in clinical trials. In addition, UCA1 has been implicated in the acquired resistance to EGFR-TKIs in EGFR-mutant NSCLC that did not include a T790M mutation [8]. Thus, the expression of UCA1 should be evaluated before patients receive EGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…However resistance to this treatment is often acquired, most commonly via a secondary T790M mutation. Cheng et al found that the lncRNA UCA1 was upregulated in resistant cells, and that overexpression of UCA1 was associated with shorter progression-free survival (PFS) in non-resistant cells [8]. Furthermore, UCA1 knockdown restored sensitivity to gefitinib in acquired-resistant NSCLC cells without the T790M mutation, and inhibited the activation of the AKT/mTOR pathway and epithelial-mesenchymal transition.…”
Section: Introductionmentioning
confidence: 99%
“…Together, ANRIL is involved in the oncogenesis of NSCLC UCA1 UCA1 (Human urothelial Carcinoma Associated 1), an lncRNA was first identified in human bladder carcinoma with oncogenic activity [36]. Cheng et al showed that UCA1 induced NSCLC cancer cells acquired resistance to EGFR-TKIs by activating the AKT/mTOR pathway and EMT [37]. A recent study from Nie found that LncRNA-UCA1 exerts oncogenic functions in NSCLC by targeting miR-193a-3p [38].…”
Section: Anrilmentioning
confidence: 99%